Data journalism and its impact on transparency and accountability in modern news: An applied study on journalists working in Saudi media institutions (visual, audio, print, and electronic) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to determine the extent of the impact of data journalism on transparency and accountability in modern news, to determine the extent of the impact of data journalism in its dimensions on transparency in modern news in Saudi Arabia, to determine the extent of the impact of data journalism on accountability in modern news in Saudi Arabia, to determine the extent of the impact of data journalism on the possibility of verifying sources in modern news in Saudi Arabia, to determine the extent of the impact of data journalism on stimulating journalistic accountability in modern news in Saudi Arabia, and to determine the extent of the impact of data journalism on the credibility of modern news in modern news in Saudi Arabia. The descriptive survey approach was used in the study, and the study population consisted of all journalists working in Saudi media institutions (visual, audio, print, and electronic), in addition to editors-in-chief, news directors, and those responsible for data journalism in these institutions. The study used a questionnaire as a tool, and statistical methods represented by the Statistical Package for the Social Sciences (SPSS) program will be used. The study expects the following results: There is an impact between data journalism in its dimensions (data collection, data analysis, Data visualization, data verification) and source transparency in Saudi Arabia's modern news. There is an impact between data journalism in its dimensions and methodology transparency in Saudi Arabia's modern news. There is an impact between data journalism in its dimensions and journalist accountability in Saudi Arabia's modern news. There is an impact between data journalism in its dimensions and media accountability in Saudi Arabia's modern news.
Keywords: Data Journalism; Transparency; Accountability; Modern News